1997
DOI: 10.1046/j.1365-2036.1997.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

A serologic survey of Helicobacter pylori infection in 3281 Italian patients endoscoped for upper gastrointestinal symptoms

Abstract: Aim:To assess the seroprevalence of Helicobacter pylori infection in a large series of patients with upper gastrointestinal symptoms referred for their first upper gastrointestinal endoscopy, and to evaluate any association with disease. Methods: A large survey of 3281 dyspeptic patients undergoing their first endoscopic examination was undertaken, involving 93 centres in Italy. A blood sample was taken from each participant, for measuring IgG antibodies against H. pylori using a commercially available kit, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…63 The results of a large multicentre study carried out in Italy involving over 3000 patients examined by endoscopy in more than 90 endoscopy units have recently been published. 64 CagA prevalence was assessed by ELISA in this large population, and the preliminary results in over 1300 patients confirm the association between CagA and major gastroduodenal pathology (table 6).…”
Section: Serological Markers Of Pathogenicitysupporting
confidence: 57%
“…63 The results of a large multicentre study carried out in Italy involving over 3000 patients examined by endoscopy in more than 90 endoscopy units have recently been published. 64 CagA prevalence was assessed by ELISA in this large population, and the preliminary results in over 1300 patients confirm the association between CagA and major gastroduodenal pathology (table 6).…”
Section: Serological Markers Of Pathogenicitysupporting
confidence: 57%
“…Education level was used as a surrogate measure of socio-economic status as reported previously. 28,29 An inverse relationship between educational attainment and infection in the overall population was seen in univariate analysis, showing more risk for healthcare personnel with %8 years of education compared with staff with a university education (Table II). As reported in Table I, in the subgroup of general medical staff, personnel with a university education showed a significantly lower prevalence of infection (P!0.01) compared with personnel with a lower education level.…”
Section: Study Population and H Pylori Infectionmentioning
confidence: 93%
“…A cut off antibody titre of 10 μg/ml was used to classify subjects as positive or negative, as recommended by the manufacturer (sensitivity 96%, specificity 93%) 28. The same IgG antibody assay has been recently used in another multicentre Italian study and showed a sensitivity of 98% and specificity of 78% when compared with a single Giemsa stained histology specimen 29. To test assay reliability we analysed about 1 in 40 samples twice, with the laboratory blinded to the previous result.…”
Section: Participants and Methodsmentioning
confidence: 99%